Базиконические сенсиллы на антеннах самцов комара Culex pipiens molestus Forsk. (Diptera, Culicidae) - Смолина, Н.А. (Вестник зоологии, 1981)
Two types of basiconic sensilla on the Culex pipiens molestus male antennae are described. They were found by supravital methylene blue staining method.